2018
DOI: 10.1016/j.nicl.2018.02.012
|View full text |Cite
|
Sign up to set email alerts
|

Altered functional connectivity differs in stroke survivors with impaired touch sensation following left and right hemisphere lesions

Abstract: One in two survivors experience impairment in touch sensation after stroke. The nature of this impairment is likely associated with changes associated with the functional somatosensory network of the brain; however few studies have examined this. In particular, the impact of lesioned hemisphere has not been investigated. We examined resting state functional connectivity in 28 stroke survivors, 14 with left hemisphere and 14 with right hemisphere lesion, and 14 healthy controls. Contra-lesional hands showed sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
45
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 37 publications
(49 citation statements)
references
References 99 publications
2
45
0
2
Order By: Relevance
“…For example, a stroke survivor with an infarct in the right hemisphere affecting S2 might not only experience the typically expected impairment of sensation in the contralateral hand (i.e., LH), but also impairment in the ipsilateral right hand; as has been described clinically (2). Further, recent evidence of altered functional connectivity in stroke survivors with impaired touch sensation following left or right hemisphere lesions, highlighted increased laterality indices in ipsilateral (contralesional) S2 relative to healthy controls following lesion of either hemisphere (109). Further, functional connectivity research has demonstrated that an increase in connectivity from contralesional S2 to contralesional thalamus correlates with better somatosensory function 6-months post-stroke (110).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, a stroke survivor with an infarct in the right hemisphere affecting S2 might not only experience the typically expected impairment of sensation in the contralateral hand (i.e., LH), but also impairment in the ipsilateral right hand; as has been described clinically (2). Further, recent evidence of altered functional connectivity in stroke survivors with impaired touch sensation following left or right hemisphere lesions, highlighted increased laterality indices in ipsilateral (contralesional) S2 relative to healthy controls following lesion of either hemisphere (109). Further, functional connectivity research has demonstrated that an increase in connectivity from contralesional S2 to contralesional thalamus correlates with better somatosensory function 6-months post-stroke (110).…”
Section: Discussionmentioning
confidence: 99%
“…Each of the regions identified above have been implicated in stroke tactile impairment and recovery, potentially highlighting their broader importance. For example, change in functional connectivity from ipsilesional right S1 to right inferior parietal lobe was found in stroke survivors with impaired touch sensation compared to healthy controls (109). In addition, increased interhemispheric connectivity between the S2 region of interest and somatosensory association cortex (involving insula, parietal operculum and SMG) and temporal gyrus was found in healthy age-matched controls compared to stroke survivors with tactile deficits (109).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Baseline data from existing cohorts of stroke survivors who were assessed on the fTORT were extracted and pooled. This included data from 115 stroke survivors who were enrolled in the following studies: SENSe ( S tudy of the E ffectiveness of N eurorehabilitation on Se nsation; n = 52) ( Carey et al, 2011 ), CoNNECT ( Co nnecting N ew N etworks for E veryday C ontact through T ouch; n = 45) ( Carey, 2013 ; Goodin et al, 2018 ), and IN_Touch ( I maging N europlasticity of Touch ; n = 18) ( Bannister et al, 2015 ; Carey et al, 2016a ). There were no overlapping participants across studies.…”
Section: Methodsmentioning
confidence: 99%
“…A customised data cleaning pipeline optimised for preprocessing of stroke data was constructed [51]. The pipeline used functions from DCMstack (https://github.com/moloney/dcmstack), Analysis of Functional NeuroImages (AFNI) [52], SPM12 v6685 (http://www.fil.ion.ucl.ac.uk/spm/software/spm12/), Advanced Normalization Tools (ANTs) [53], Numpy [54], Scipy [55], and Nibabel (https://github.com/nipy/nibabel), combined under the NiPype framework [56].…”
Section: Methodsmentioning
confidence: 99%